Water‐binding‐mediated gelation/crystallization and thermosensitive superchirality - Xing, Pengyao (2020)
Determination of molecular structural parameters of hydrophobic cholesterol–naphthalimide conjugates for water binding capabilities as well as their moisture‐sensitive supramolecular self‐assembly were revealed. Water binding was a key factor in leading trace water‐induced crystallization against gelation in apolar solvent. Ordered water molecules entrapped in self‐assembly arrays revealed by crystal structures behave as hydrogen‐bonding linkers to facilitate three‐dimensional growth into crystals rather than one‐dimensional gel nanofibers. Water binding was also reflected on the supramolecular chirality inversion of vesicle self‐assembly in aqueous media via heating‐induced dehydration. Structural parameters that favor water binding were evaluated in detail, which could help rationally design organic building units for advancing soft materials, crystal engineering, and chiral recognition.